ANALYZING SUCCESSION MANAGEMENT PRACTISE IN THE CONTEXT OF ORGANIZATIONAL SURVIVAL: A QUALITATIVE APPROACH - Fadeyi, Olatunji; Oladele, Kehinde; Imhonopi, David; Nwachukwu, Chijioke (International Journal for Quality Research, 2019)
Qualitative data analysis methods are becoming more and more useful in management sciences. In this paper, an attempt is made to qualitatively ascertain the extent to which effective management succession influences organizational survival. An open-ended interview schedule with 15 questions was administered on 15 randomly selected individuals belonging to top, mid and low level management cadre across 5 money deposit banks in Nigeria. Qualitative content analysis was used to carry out coding of the responses. Cohen Kappa (?) inter-coder reliability test of trustworthiness gave a coding consistency value of 0.86, showing a near-perfect agreement. The final themes generated include; succession ingredients; succession results, and succession checks. It was found that for succession to truly drive an organization towards survival, certain key inputs, otherwise known as ingredients must be in place. Furthermore, the many short-comings in the process of succession must be checked and corrected. If rightly corrected, succession checks could help gain positive results, however, if not carefully monitored, results could be negative.